Building cross-platform apps using Titanium, Alloy, and Appcelerator cloud services - Saunders, Aaron (John Wiley & Sons, 2015)
Skip Objective-C and Java to get your app to market faster, using the skills you already have Building Cross-Platform Apps using Titanium, Alloy, andAppcelerator Cloud Services shows you how to buildcross-platform iOS and Android apps without learning Objective-C orJava. With detailed guidance given toward using the Titanium MobilePlatform and Appcelerator Cloud Services, you will quickly developthe skills to build real, native apps' not webapps'using existing HTML, CSS, and JavaScript know-how. Thisguide takes you step-by-step through the creation of aphoto-sharing app that leverages the power of Appcelerator's cloudplatform, and establishes fundamental concepts before addingadvanced techniques. Coverage extends beyond the developmentprocess to include expert advice for deployment on the App Store orGoogle Play, and more. The mobile app market is estimated at over $2.4 billion peryear. These apps were traditionally built using Objective-C orJava, which can be complex and daunting to learn. Now you can useJavaScript on the Titanium framework to build amazing apps that runnative on iOS and Android devices, and get your app to marketfaster with this guide.-Integrate Cloud Services APIs into the app framework andUI -Set up user accounts, and capture and store photos -Work with location-based services and share via socialmedia -Deploy on the App Store, Google Play, and more When a great idea is in the works, no one wants to put it onhold to learn an entirely new skillset. Now there's an alternative. Get that app to market fast, using existing skills and powerful newtools, and grab a piece of that multi-billion-dollar market. Building Cross-Platform Apps using Titanium, Alloy, andAppcelerator Cloud Services is your ticket to the front of theline.